Dvoumnost napredka (Založba Univerze v Ljubljani, 2024)
How should we think about the major changes that happened with the onset of modernity? How was progress conceptualized in different historical epochs? To what extent did notions of progress differ between different regions and different social groups – and what can we learn from such comparisons? How should we understand the transitions between different political regimes, particularly in the 20th century?These are some of the issues that are going to be discussed on the PhD and Postdoc Workshop, ‘The Ambivalence of Progress’.